Putting agriculture at the heart of development in Africa - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
As Africa has moved toward country ownership and leadership in agricultural development, IFPRI has provided essential data, research, policy analysis, and capacity strengthening. Early research on the links between government policies, agricultural growth, hunger, and poverty laid the foundation for support to continental, regional, and country-level initiatives.